Diversidade genética de Anadenanthera peregrina (L.) Speg. (Fabaceae) em área de plantio no sul do Espírito Santo - Cortelete, Maressa Albuquerque (2016)
The development of a forest species aiming the production in plantations demands works of pre-breeding and the development of silvicultural techniques. Obtaining information that reveals the levels of genetic diversity, as well as the processes that maintain it, is necessary when it is desired to practice conservation and breeding measures. Knowing and understanding how genetic diversity is structured in geographic space contributes to the understanding of the evolutionary history and the population dynamics of the species. For most of the species of the Atlantic Forest Biome, there is still little knowledge about genetic diversity for possible breeding programs, so this work aims to generate information about the genetic variability of Anadenanthera peregrina (angico-vermelho), established in an area of planted forest in the southern region of Espírito Santo, through molecular markers. Leaf tissue samples from each plant were used for the extraction and purification of the DNA. The molecular data record was made from polymorphisms of the PCR products among genotypes, detected by 10% polyacrylamide electrophoresis. Six SSR molecular markers were used and the number, richness and frequency of alleles, frequencies and genotypic distributions, Hardy-Weinberg equilibrium deviations and fixation index (F) were calculated for each locus. The values of genetic similarity between individuals in the population were estimated by the square of the mean Euclidean distance from the molecular data. Estimates of genetic dissimilarity (dii ') were made according to the arithmetic complement of the simple coincidence coefficient and organized into matrices, to be used in cluster analysis by the mean linkage between groups (UPGMA). The inference of genetic groups in the individuals of the population was made using a Bayesian Monte Carlo Markov Chain (MCMC) approach. Were selected 166 individuals, each tree it had the georeferential location (by GPS) and it was characterized dendometrically (DBH and total height). All loci presented polymorphism and the number of alleles per locus ranged from 4 to 9. The mean value of PIC was informative (0.72), the expected and observed mean heterozygosity values were 0.76 and 0.74 respectively, and the ratio of these values generated negative fixation indexes (FIS) at some loci, indicating the excess of heterozygotes in the population, for the Acol 18 and Acol 18 loci, the values were positive. The genetic diversity (H ') had values equal to the expected proportion of heterozygotes (He) - 0.76, showing that the population is in Hardy-Weinberg equilibrium. The allelic richness was on average 7.64 alleles per loco. The dii 'estimates were 100% in 89 access pairs and the lowest dii' value was between 82 and 83 individuals (7.14%). The dendrogram obtained by the UPGMA method shows that the population is structured in 6 groups, and the analysis by Bayesian approach confirms that the population is structured in only 2 genetic groups (K = 2). By means of these two methods it is possible the orientation for selection of individuals with smaller or greater genetic variability, thus obtaining lots of seeds with good genetic variability for a future seed orchard